Applying the Trikora Spirit in Public Administration Practices to Build the Welfare of the Papuan People - Almuchalif Suryo; Samuel Lumban Toruan; Adnan Majid; Joni Widjayanto (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This study aims to analyze the application of the Trikora spirit in public administration practices to build the welfare of the Papuan people. The research method used in this study is a qualitative approach by conducting a literature review. The results of this study show that the Trikora spirit can be applied in public administration practices, particularly in optimizing governance, coordination, and supervision, as well as in improving the implementation of programs and policies in Papua. Various efforts have been made by the government to resolve existing problems through the enactment of Law No. 21 of 2001 concerning Special Autonomy for the Province of Papua. However, twenty years after the implementation of special autonomy, the results are still not optimal. This is because, among other things, governance is still not optimal, there is no supervision and assistance from the center, and programs from ministries and institutions have not been well coordinated and integrated. I hope that the mobilization of all potential national resources, the spirit of one unit, synchronization and coordination as well as command and control when the Trikora to seize West Irian need to be imitated and continued to build the development of Papua's welfare